Mobile Application to identify and recognize emotions for children with autism: A systematic review - Al-Saadi, Abdelrahman Mohammed; Al-Thani, Dena (Frontiers in Child and Adolescent Psychiatry, 2023)
Emotions are a vital component of human interaction. Children with Autism Spectrum Disorder (ASD) face severe difficulties in sensing and interpreting the emotions of others, as well as responding emotionally appropriately. Developers are producing a plethora of mobile applications to assist ASD children in improving their facial expression detection and reaction abilities, hence increasing their independence.